Relation Between Pulpal Neuropeptides and Dental Caries - Kangarlou Haghighi, Ali; Nafarzadeh, Shima; Shantiaee, Yazdan; Naseri, Mandana; Ahangari, Zohreh (Iranian Endodontic Journal, 2010)
INTRODUCTION: Dental pulp has neural fibers that produce neuropeptides like Substance P (SP) and calcitonin gene-related peptide (CGRP). The inflammation of dental pulp can lead to an increase amount of SP and CGRP release, especially in symptomatic irreversible pulpitis. Therefore, it can be assumed that neuropeptides have some role in the progression of inflammation of the dental pulp. The aim of this study was to determine the relation between the presence and concentration of neuropeptides in dental pulps of carious teeth caries. MATERIALS AND METHODS: For this purpose, pulpal tissues were collected from 40 teeth (20 carious and 20 intact). Pulpal samples were cultured for 72 hours. ELISA reader was used for the detection of SP and CGRP in supernatant fluids. Statistical analysis was made by Mann-Whitney U and Chi square tests. RESULTS: SP and CGRP were present in 65% and 20% of inflamed pulpal samples, respectively and 40% and 5% of normal pulpal samples, respectively. Level of SP was significantly higher in inflamed pulp samples compared to intact pulps; however, there was no statistical difference when the other groups and neuropeptides were compared. The mean concentration of SP in normal pulps was 3.4 times greater than that of CGRP; interestingly in inflamed pulps the concentration of SP was 22.3 times greater than CGRP. CONCLUSION: We can conclude that in inflamed dental pulps, the concentration of SP is higher than CGRP. It can be hypothesized that CGRP has less effect on the inflammatory changes of dental pulps.